The truth about women - Crispin, Edmund 1921-1978 (Studiocanal, 2023)
"The truth about women (1957), which Muriel Box called her most personal film, reveals the complex lives of women and the assertion that women can and should be 'an equal partner in the business of life'."
Bildformat: 1.37:1
Extras: "An equal partner in the business of life: Muriel Box & The truth about women" ; "The women behind the picture: archive interview with Muriel Box, Part 2", "Behind the scenes stills gallery", Original trailer
Original 1957
Keywords: Film; DVD-Video